Treatment in Patients DRESS (Drug Reaction With Eosinophilia And Systemic Symptoms) : Case Report - Sigit Prakoeswa, Flora Ramona; Rosyida, Hindun Luthfia; Ariyanti, Rika (Asian Journal of Social and Humanities, 2023)
Drug reactions with eosinophilia and systemic symptom syndrome (DRESS) are rare and potentially life-threatening severe skin adverse reactions (SCAR) The mean age at diagnosis is approximately 50-55 years and less than 10% of patients are under 20 years men : women 0.7-0.8. All drugs used by the patient during DRESS should be stopped immediately. Complications of DRESS are myocarditis, Pneumocystis jiroveciipneumonia, sepsis, liver failure, and gastro-intestinal bleeding. Systemic corticosteroids (prednisolone 1 mg/kg/day) are the gold standard of treatment in the acute phase of patients with severe organ involvement. Therefore, the importance of appropriate therapy to reduce the occurrence of complications from DRESS disease.